2021
DOI: 10.1142/s1088424621500486
|View full text |Cite
|
Sign up to set email alerts
|

meso-Carbazole substituted palladium porphyrins: Efficient catalysts for visible light induced oxidation of aldehydes

Abstract: The A3B and A2B2 type porphyrins having [Formula: see text]-butylcarbazole and [Formula: see text]-cyanophenyl groups are synthesized and characterized. Their palladium complexes have also been prepared and utilized as catalysts for the photo-oxidation reactions of aromatic aldehydes in good yields. Pd(II)porphyrins displayed decent phosphorescence at [Formula: see text]670 nm and were able to generate singlet oxygen upon light irradiation. The calculated singlet oxygen quantum yields for Pd(II)porphyrins were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Generally, aromatic aldehydes with electron withdrawing groups gave better yields of the oxidised products. 41,42 These observations clearly suggest that the Pd-dipyrrinato complexes reported in this work have the potential to be developed as efficient catalysts for such photo-oxidation of organic compounds.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Generally, aromatic aldehydes with electron withdrawing groups gave better yields of the oxidised products. 41,42 These observations clearly suggest that the Pd-dipyrrinato complexes reported in this work have the potential to be developed as efficient catalysts for such photo-oxidation of organic compounds.…”
Section: Resultsmentioning
confidence: 56%
“…Previously, the Pd(II)porphyrins have been shown to generate a good amount of singlet oxygen, which in turn was used to catalyse the photo-oxidation of organic compounds. 41,42 Similarly, the Pd3 complex was tested for the photo-catalytic application of the aerobic oxidation of aromatic aldehydes at room temperature, and the data are summarized in Table 3. The oxidation reactions were carried out in acetonitrile using the Pd3 complex as a photo-catalyst; the duration of the reaction was 1-6 h. Acetonitrile was selected as a solvent for such photooxidation reactions, as chloroform was quickly evaporated during the process.…”
Section: Singlet Oxygen Generation and Photocatalysismentioning
confidence: 99%
“…DPBF is insoluble in plain water, so all tests were performed in 50:50 (v/v) water and ethanol mixture. Rose Bengal was used as a standard photosensitizer. , The stock solution of DPBF and Rose Bengal was prepared. The solutions were covered by aluminum foil to avoid light exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Rose Bengal was used as a standard photosensitizer. 31,32 The stock solution of DPBF and Rose Bengal was prepared. The solutions were covered by aluminum foil to avoid light exposure.…”
Section: Synthesis Of Porphyrin 4-(2-(2-methoxyethoxymentioning
confidence: 99%
“…Gupta and colleagues accomplished C−H arylation of heteroarenes using zinc‐coordinated carbazole‐linked porphyrin‐based photoredox catalysts ( Zn‐porphyrin ) (Figure 21, Table 1L). [43] This work exemplified the concept with 28 instances of various substituted aryl amines, as well as pyrrole, furan, and thiophenes. They found that the substrates containing electron‐donating group exhibited reduced reactivity when compared with those containing electron‐accepting groups.…”
Section: Examplesmentioning
confidence: 98%